CARBON-BASED MATERIALS FOR HEALTHCARE MICRO-DEVICES - Roxana Marinescu; Bogdan Catalin Serban; Niculae Dumbravescu; Viorel Avramescu; Cornel Cobianu; Octavian Buiu (Nonconventional Technologies Review, 2019)
Microtechnology is one of the key technologies supporting the behaviour for healthier life, including disease prevention and faster healing. An amazing demand for autonomous micro-devices in “healthcare” field is raising the need for miniaturized power sources. These micro-devices need to be made of durable, hard but flexible materials and also easy to use materials. For all these demands, a research on carbon-based materials was made. So, it was found that combinations of carbon-based materials can be made, because this need means more power, more strength and more rapid time of response. Graphene, Carbon Nanohorns (CNHs) and Carbon Nanotubes (CNTs) were the three carbon-based materials studied in this research and their properties of being adaptable to micro-devices for healthcare.